2020
DOI: 10.17485/ijst/v13i22.862
|View full text |Cite
|
Sign up to set email alerts
|

Impact of small and medium enterprises on employment generation in Kaduna State Nigeria

Abstract: Aim/objectives: To examine the impact small and medium enterprises have on employment generation in Kaduna state, Nigeria and devise new ways in boosting employment generation by enterprises. Methods/Statistical analysis: Primary data is utilised with the help of a questionnaire; a survey is carried out from 5 selected SMEs having a sample size of 1,000 respondents with 200 respondents in each of the 5 selected SMEs. The variables in concerned were analysed using the Kaiser Varimax Rotation for factor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…The MSMEs are believed to be contributing greatly to the economic growth and development of every economy. For a long time, SMEs are known to be instruments for economic growth and development; hence the World Bank Group concentrates on their development with the view to promoting employment generation, poverty eradication and economic growth (Shettima, 2017). The role of SMEs to economic development, poverty alleviation, provision of employment, output, innovation in technology and uplifting in social status and standard is well-known in both developed and developing economies (Eniola and Ektebang, 2014).…”
Section: Existing Programsmentioning
confidence: 99%
“…The MSMEs are believed to be contributing greatly to the economic growth and development of every economy. For a long time, SMEs are known to be instruments for economic growth and development; hence the World Bank Group concentrates on their development with the view to promoting employment generation, poverty eradication and economic growth (Shettima, 2017). The role of SMEs to economic development, poverty alleviation, provision of employment, output, innovation in technology and uplifting in social status and standard is well-known in both developed and developing economies (Eniola and Ektebang, 2014).…”
Section: Existing Programsmentioning
confidence: 99%
“…These institutions include SMEDAN, NEDEP, YOUWIN. These agencies apart from providing financial assistance, loans also provide capacity building for owners and managers of SMEs (Shettima, 2017). Federal Industrial Research, Oshodi (FIRO); Nigeria Small and Medium Enterprises, Equity Investment Scheme (SMEEIS), Industrial Development Centres (IDC).…”
Section: Role Of Government In Human Capacity Buildingmentioning
confidence: 99%
“…On the digital platform, MSMEs not only survived but also grew (Tempo, 2021). Research by Shettima & Sharma (2012), Turais (2020) and Kawira et al (2019) stated that technology affected the performance of MSMEs, while the results of research done by Kagnew Abebaw (2018) and Ifeoma & Chikwado (2019) showed that technology did not affect the performance of MSMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Performance can be defined as the result of the efforts made by the owners and managers of the company. There are many factors affect MSME performance, including product innovation (Rezaei & Ortt, 2018;Cho and Lee, 2018;Dahlan et al, 2023;Le et al, 2023a;Yaskun et al, 2023), financial literacy (Rumain et al, 2021;Rosliyati & Iskandar, 2022;Rahadjeng et al, 2023;Rofiqoh et al, 2023;Saskia et al, 2023) and technology utilization (Shettima & Sharma, 2012;Turais, 2020;Susilatri et al, 2022;Teng et al, 2022;Alsedrah, 2023;Haq & Huo, 2023). https://doi.org/10.…”
Section: Introductionmentioning
confidence: 99%